Pengembangan Teknik Fotografi Bagi UMKM Di Mojokerto Untuk Meningkatkan Kesadaran Merek - Rizky Pratama Ramadhani; Dhani Ichsanuddin Nur (Universitas 45 Surabaya, 2023)
With the level of technological development, the human lifestyle has changed even more and has become a necessity such as the internet. The internet is utilized by humans in everything that can help all human needs, including being utilized by UMKM players to carry out digital marketing. The development of technology allows humans to see various product images only through devices, one of which is through social media platforms so that good photography skills are needed. The method used was a group discussion forum and interviews accompanied by a live demonstration. Simple photography skills training using a smartphone application in the form of an open camera assisted by an ai website, namely pebblely. In this training, it is hoped that UMKM players can independently utilize technological developments and updates that can support product promotion on social media.